Development of a T‐cell receptor mimic antibody targeting a novel Wilms tumor 1‐derived peptide and analysis of its specificity - Kurosawa, Nobuyuki (Cancer Sci, 2020)
Wilms tumor 1 (WT1) is an intracellular tumor‐associated antigen that remains inaccessible to antibodies. Recently, T‐cell receptor (TCR) mimic antibodies (TCRm‐Abs), which recognize peptides loaded on human leukocyte antigen (HLA) with higher specificity and affinity than TCR, have been developed as a new antibody class that can target intracellular antigens. To expand the therapeutic targets in tumors with WT1, we developed TCRm‐Abs targeting a novel HLA‐A*02:01‐restricted peptide, WT1C (ALLPAVPSL), and validated their specificity using multiple techniques. Screening of these antibodies by ELISA with a panel of peptide/HLA complexes and by glycine scanning of peptide‐pulsed T2 cells identified one specific clone, #25‐8. Despite the low risk for eliciting broad cross–reactivity of this TCRm‐Ab, analysis of a panel of cell lines, in conjunction with exogenous expression of either or both the HLA‐A*02:01 and WT1 genes in HeLa cells, revealed that #25‐8 reacts with WT1C but also with unknown peptides in the context of HLA‐A*02:01. This potentially dangerous cross–reactivity was confirmed through analysis using chimeric antigen receptor T‐cells carrying the single‐chain variable fragment of #25‐8, which targets WT1‐negative HeLa/A02 cells. To determine the cross–reactive profiles of #25‐8, we applied the PresentER antigen presentation platform with the #25‐8‐recognition motif, which enables the identification of potential off–target peptides expressed in the human proteome. Our results demonstrate the potential of TCRm‐Abs to target a variety of peptides in the context of HLA but also depict the need for systematic validation to identify the cross–reactive peptides for the prediction of off–target toxicity in future clinical translation.